Molecular Docking, Synthesis, and, Biological Activity of New Diclofenac Derivatives Incorporating 1,2,4-Triazole Ring as a Promising Antibacterial Agents - Doohee, Alyaa N.; Naser, Noor H.; AL-GBURI, Karrar (Iraqi Journal of Pharmaceutical Sciences, 2025)
NSAIDs, recently have been shown to exert a wide variety of biological activities, such as antibacterial, antifungal, antioxidant, and anticancer activity. The triazole ring has various pharmacological activities of tetrazole ring, anticancer, antidiabetic, antifungal, antioxidant, anticonvulsant, antiviral, and antibacterial properties. Hence, the aim of this study was to design, synthesize, molecular docking, and assess the antibacterial activity of new diclofenac derivatives incorporating a 1,2,4-triazole ring. Molecular docking studies were carried out using MOE 2015 software using a standard protocol. The new diclofenac derivatives (VIa-d) were synthesized by esterifying diclofenac, reacting the product with hydrated hydrazine and carbon disulfide, and cyclization to form a 1,2,4-triazole ring. Finally, the reaction of the benzoyl chloride derivatives with the primary amino group on the synthesized triazole ring via a nucleophilic substitution reaction. In vitro antibacterial activity of diclofenac, and the synthesized compounds were evaluated by using the agar-well diffusion method. Compounds (VIa-d) have shown a higher binding score than the reference ligand (Topotecan) against Human DNA topoisomerase I (PDB: 1K4T), while they were nearly identical to the reference ligand (levofloxacin) against type IV topoisomerase from S. pneumoniae (PDB: 3RAE). All of the compounds inhibited growth of the Staphylococcus aureus and Escherichia coli, with compound VId exhibiting the highest level of activity.